ROSUS 2019: računalniška obdelava slik in njena uporaba v Sloveniji 2019 : zbornik 14. strokovne konference (University of Maribor Press, 2019)
ROSUS 2019 : Computer image processing and its application in Slovenia 2019: Proceedings of the 14th Professional Conference. ROSUS 2019 – Computer image processing and its application in Slovenia 2019 is a professional conference that, since 2006, has been organised every year by the Institute of Computer Science of the Faculty of Electrical Engineering and Computer Science, University of Maribor. The conference connects researchers in the fields of Image Processing and Machine Vision with users of this knowledge, whereby users are coming from diverse industrial environments, such as Biomedicine, Sport, Entertainment, and related fields. The proceedings of ROSUS 2019 combines 14 scientific articles by 50 authors, including invited lecture and four demonstration articles. Contributions represent the latest achievements of Slovenian experts in the fields of Image Processing and Vision, and also highlight trends and novelties in these areas. Great emphasis is on promotion of the economic usefulness of Image Processing and Vision applications in the Slovenian region. Namely, such software, due to high precision, robustness, and exceptional speed in information processing, provides new opportunities for penetration on the high technologies market.